Development and psychometric testing of a competency of nursing process questionnaire - Virya Koy; Jintana Yunibhand; Andrew Rauth; Nicholas Bircher; Manila Prak; Richard Henker (Elsevier, 2023)
Objectives: This study aimed to develop and evaluate a competency of nursing process questionnaire (CNPQ) for registered nurses in Cambodia. Methods: Guided by the nursing process, an initial questionnaire was generated through focus group discussion, literature review, and the expert consultation. Finally, the validity and reliability of the questionnaire were validated through a questionnaire survey online of 260 registered nurses selected from Complimentary Package Activities 1, 2, 3, and national hospitals from January to February 2022 in five geographic areas of Cambodia. Results: The content validity index was 1.00. The Cronbach's α coefficient for the whole questionnaire was 0.963, and the range for the five dimensions was 0.963-0.964, which shows that the questions were consistent. The test-retest reliability was 0.769. The exploratory factor analysis led to a list of 24 items that were grouped into five dimensions: assessment, diagnosis, planning, implementation, and evaluation. The cumulative variance contribution rate was 70.08%. Conclusions: The CNPQ developed in this study showed good reliability and validity and can be used to assess the competency of registered nurses by themselves and help nursing managers to develop the relevant policies.